Suppression of leaf growth and photosynthetic capacity as an acclimation strategy to nitrogen deficiency in a nitrogen-sensitive and shade-tolerant plant Panax notoginseng - Zhu Cun; Sheng-Pu Shuang; Jin-Yan Zhang; Jie Hong; Hong-Min Wu; Jing Yang; Hong-Chao Zhao; Li-Lin Gao; Jun-Wen Chen (Journal of Plant Interactions, 2022)
Photosynthesis is susceptible in response to nitrogen (N) deficiency. However, the acclimation of shade-tolerant and high-N sensitive species to N deficiency is unclear. Leaf morpho-physiological traits, photosynthetic performance related parameters were examined in a shade-tolerant and high-N sensitive species P. notoginseng grown under different N levels. Lower N content and Chl content were recorded in the N0-grown P. notoginseng. The maximum values of leaf morpho-physiological traits, photosynthetic rate, and photosynthetic N use efficiency (PNUE) were obtained in the N15-grown P. notoginseng. Coefficients for leaf N allocation into the carboxylation and light-harvesting system components in the N0-grown plants were significantly higher than others. N0 and N7.5 plants showed higher K phase. N addition decreased the absorption and capture of the light energy per unit area (ABS/RC and TRO/RC) and non-photochemical quenching (NPQ). Photochemical quenching (qP), electron transport rate (ETR), and effective quantum yield of photosystem II (ϕPSII) were reduced in the N0-grown plants. The reduction of light-harvesting and utilization capacity not only leads to a decrease in PNUE, but also induces the damage of PSII reaction center. Overall, the inhibition of leaf growth and photosynthetic capacity is an essential strategy for high-N sensitive and shade-tolerant plants in response to N deficiency.